ANALISIS PENGARUH TINGKAT KESEHATAN, TINGKAT PENDIDIKAN, DAN UPAH TERHADAP PRODUKTIVITAS TENAGA KERJA DI INDONESIA - Putri, Yohanna Adisti Krisna Dwi; Kusreni, Sri (Jurnal Ilmu Ekonomi dan Pembangunan, 2017)
This research aims to analyze the impact of variable health level proxied by life expectancy, level of education which proxied by workers with graduate primary education, secondary education and tertiary education, and the provincial minimum wage on labor productivity in 33 provinces in Indonesia from 2008 to 2013. The analytical method that used is panel data regression (pooled data) with the Fixed Effect Model approach. Results of panel data regression analysis in this research showed that level of health, level of education, and the minimum wage is simultaneously significant positive effect on labor productivity. Partially, level of health is significant and positive impact on labor productivity, while the level of education and the minimum wage has no significant impact on labor productivity in Indonesia.